Applying MAPPs Assays to Assess Drug Immunogenicity - Karle, Anette C. (Frontiers in Immunology, 2020)
Immunogenicity against biotherapeutic proteins (BPs) and the potential outcome for the patient are difficult to predict. In vitro assays that can help to assess the immunogenic potential of BPs are not yet used routinely during drug development. MAPPs (MHC associated peptide proteomics) is one of the assays best characterized regarding its value for immunogenicity potential assessment. This review is focusing on recent studies that have employed human HLA class II-MAPPs assays to rank biotherapeutic candidates, investigate clinical immunogenicity and understand mechanistic root causes of immunogenicity. Advantages and challenges of the technology are discussed as well as the different areas of application.